Inpatient statin use and stroke recurrence in patients with or without diabetes mellitus. (3rd October 2019) - Zhang, Xing; Li, Shu-Ya; Jing, Jing; Pan, Yue-Song; Yan, Hong-Yi; Meng, Xia; Zhao, Xing-Quan; Liu, Li-Ping; Wang, Chun-Xue; Wang, Yi-Long; Wang, Yong-Jun
ABSTRACT: Objectives : Although statin therapy is associated with lower recurrence in patients with acute ischaemic stroke, data-evaluating associations between inpatient statin use and stroke recurrence in diabetic patients after acute stroke onset are limited. Methods : This study was based on population data from the Chinese National Stroke Registry. Patients with acute ischaemic stroke and no history of statin therapy were selected. Individuals treated regularly with any type or dosage of statins during acute hospitalization were defined as having inpatient statin therapy. The subjects were divided into two groups according to statin use status during acute hospitalization. Multivariate logistic regression analysis was used to analyse the associations between statin use and stroke recurrence in patients with or without diabetes. Results : A total of 11, 429 patients, 2341 (20.48%) with diabetes, were selected for analysis. Statin therapy during hospitalization was documented in 4982 (43.59%). Logistic analysis showed no significant associations between inpatient statin use and stroke recurrence in diabetic subjects at 3 months (OR = 0.90, 95% CI = 0.69–1.16, P = 0.40) or 1 year (OR = 0.92, 95% CI = 0.74–1.16, P = 0.48), but statin use was significantly associated with lower recurrence in non-diabetic patients at both 3 months (OR = 0.80, 95% CI = 0.69–0.92, P = 0.002) and 1 year (OR = 0.82, 95% CI = 0.72–0.93, P = 0.002) after discharge. Conclusion : Inpatient statin use was associated with lower stroke recurrence in non-diabetic patients after acute ischaemic stroke, but no definite association between inpatient statin use and stroke recurrence in patients with diabetes mellitus was found.